1989
DOI: 10.1016/0014-5793(89)81050-6
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐transfer restoration by vitamin K3 in a complex III‐deficient mutant of S. cerevisiae and sequence of the corresponding cytochrome b mutation

Abstract: The yeast box-mutant W7 exhibits deficiencies in cytochrome b and in nuclear coded complex III subunits, a phenotype observed previously in a patient with mitochondriai myopathy. DNA sequence analysis of mutant W7 revealed a single base transition in the cytochrome b gene; the mutated residue Gly 131 is perfectly conserved in all known cytochromes b and belongs to the Qo domain. Mutant W7 provides a model system for evaluating the action of therapeutic agents, such as vitamin K 3 which restored NADH-oxidase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…The observed increase in NADH-oxidation by menadione in complex III inhibited fibroblasts is in agreement with the observations of Brivet-Chevillotte and Di Rago (1989), who studied the effects of menadione on NADH-oxidation in a complex IIIdeficient mutant of S. cerevisiae.…”
Section: Resultssupporting
confidence: 91%
“…The observed increase in NADH-oxidation by menadione in complex III inhibited fibroblasts is in agreement with the observations of Brivet-Chevillotte and Di Rago (1989), who studied the effects of menadione on NADH-oxidation in a complex IIIdeficient mutant of S. cerevisiae.…”
Section: Resultssupporting
confidence: 91%
“…Apparently, only menadione is able to carry out so called cytosolic‐mitochondrial electron shuttling in A. fumigatus . Accordingly, in yeast except of menadione no other quinone was able to bridge the electron transfer of NADH oxidation when complex III was inhibited (Nosoh et al ., ; Brivet‐Chevillotte and di Rago, ). Likewise, menadione restored the electron flow and ATP formation in cardiomyocytes after the inhibition of complex I with rotenone (Shneyvays et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…One-electron reduction of VK3 leads to the formation of VK3-semiquinone that in the presence of oxygen is oxidized back to VK3 while oxygen is in turn, one-electron reduced to generate Å O À 2 that causes oxidative stress and cytotoxicity. Thus, many of the early biochemical studies showed that VK3 acts as an artificial electron carrier/shunt like ubiquinone (UbQ, CoQ) in the mitochondrial respiratory chain, capable of restoring function when either of complexes I, II or III is inhibited (Slater, 1959;Kolesova et al, 1978;Brivet-Chevillotte and di Rago, 1989;Korneev et al, 1990). VK3 was also used clinically in early attempts to overcome debilitating genetic mutational deficiencies in the respiratory chain complexes of patients suffering from associated mitochondrial disease (reviewed in Mowat et al, 1999;Argov et al, 1986), although bypassing the blockages by administering electron acceptors has not proven very successful.…”
Section: Implications For Cancer Therapy and Why Mitochondria Providementioning
confidence: 99%